Integrated Counseling Study of Islamic Values and Minangkabau Culture: A Literature Review - Sukandar, Warlan; Abdul Rashid bin Abdul Aziz; Rezki Perdani Sawai (Islam Transformatif : Journal of Islamic Studies, 2024)
Cultural and religious values ​​are integral to the life of the Minangkabau people. However, many studies have not considered integrated counseling with Minangkabau values ​​and culture. For this reason, this research aims to analyze articles related to integrated counseling studies of Islamic values ​​and Minangkabau culture. This study uses a literature review approach and internet search engines such as Google Scholar, ResearchGate, Google Scholar, and Academia.edu to find articles related to the study theme. This research is the first literature review research to examine integrated counseling with Islamic values ​​and Minangkabau culture. The research results show that studies related to integrated counseling with Islamic values ​​and Minangkabau culture are still minimal. The results of this study have resulted in the discovery of eleven articles related to the theme studied. Nine articles have the theme of counseling and Minangkabau culture, and only two discuss counseling, Islam, and Minangkabau culture. The results of this research can be used as a reference for future researchers. They can also be a reference for the government to pay attention to local wisdom values ​​in solving community problems in West Sumatera.